2007
DOI: 10.1002/arch.20191
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of detoxification pathways of ingested ecdysteroids among phytophagous insects

Abstract: The metabolic pathways of ingested ecdysteroids have been investigated in three insect species, the aphid Myzus persicae and two Lepidoptera, Plodia interpunctella and Ostrinia nubilalis. M. persicae produces mainly a 22-glucoside conjugate, whereas P. interpunctella eliminates a mixture of 20E and its 3-oxo and 3-epi derivatives, both in free form and as conjugates with various fatty acids. O. nubilalis only produces fatty acyl ester conjugates. These data point out the great diversity of detoxification mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…Inactivation involves the conversion of active ecdysteroids to more polar metabolites and/or formation of conjugates. In decapods, the two major organs responsible for removing ecdysteroids from the hemolymph are the antennal gland and hepatopancreas [72]. In general, the antennal gland and peripheral tissues are responsible for the conversion of ecdysteroids to inactive polar metabolites, which are then excreted in the urine.…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation involves the conversion of active ecdysteroids to more polar metabolites and/or formation of conjugates. In decapods, the two major organs responsible for removing ecdysteroids from the hemolymph are the antennal gland and hepatopancreas [72]. In general, the antennal gland and peripheral tissues are responsible for the conversion of ecdysteroids to inactive polar metabolites, which are then excreted in the urine.…”
Section: Resultsmentioning
confidence: 99%
“…PEs are generally toxic to insects because they interfere with ecdysone signaling (Dinan 2001). Although ECB larvae can detoxify PEs by producing fatty acyl ester conjugates (Rharrabe et al 2007), we observed that larvae avoid feeding on a diet that contains PEs. Since ECB larvae and adults avoid PEs, we wondered if ECB larvae would be deterred by odorants emitted by spinach.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, the two major organs responsible for removing ecdysteroids from the hemolymph are the antennal gland and hepatopancreas (midgut gland) in decapods. The diversity of inactivation pathways in crustaceans is reminiscent to those used by insects to detoxify ecdysteroids ingested from plants (see [98] for review). The primary site for excretion of ecdysteroids is the antennal gland.…”
Section: Ecdysteroid Metabolism and Excretionmentioning
confidence: 99%